2003
DOI: 10.1590/s0100-879x2003000500012
|View full text |Cite
|
Sign up to set email alerts
|

Impaired beta-adrenergic response and decreased L-type calcium current of hypertrophied left ventricular myocytes in postinfarction heart failure

Abstract: Infarct-induced heart failure is usually associated with cardiac hypertrophy and decreased ß-adrenergic responsiveness. However, conflicting results have been reported concerning the density of L-type calcium current (I Ca(L) ), and the mechanisms underlying the decreased ß-adrenergic inotropic response. We determined I Ca(L) density, cytoplasmic calcium ([Ca 2+ ] i ) transients, and the effects of ß-adrenergic stimulation (isoproterenol) in a model of postinfarction heart failure in rats. Left ventricular myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Our findings and Aggarwal's results showed that in the early stage of heart remodeling (5-10 weeks after infarction), I CaL was significantly decreased but in the later stage, according to Gómez's result [27] , I CaL returned to normal level. Although the underlying mechanism for this phenomenon is not clear, the result implies that the heart ionic remodeling is different between early and end stage.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings and Aggarwal's results showed that in the early stage of heart remodeling (5-10 weeks after infarction), I CaL was significantly decreased but in the later stage, according to Gómez's result [27] , I CaL returned to normal level. Although the underlying mechanism for this phenomenon is not clear, the result implies that the heart ionic remodeling is different between early and end stage.…”
Section: Discussionsupporting
confidence: 72%
“…So far, the findings regarding I CaL in post-MI hypertrophic cardiomyocytes were conflicting. Gómez et al found that in ischemic cardiomyocytes, I CaL increased 1 week after MI development and restored to normal level 3 weeks till 6 months after myocardial infarction [19,27] . Saraiva et al found that the current was significantly decreased in cardiomyocytes 8-10 weeks after ligation [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, simple phenomenological models of β-adrenergic-mediated LCC and PLB phosphorylation which are able to approximate both the steadystate and dynamic isoprenaline dose responses of relevant functional data are applied. The steady-state dose response data used to parameterize the LCC phosphorylation component come from Saraiva et al [36] and are shown along with model fits in figure 2. The data are fit to a Hill equation of form…”
Section: β-Adrenergic Pathwaymentioning
confidence: 99%
“…The black line in the diagram indicates a dependency that was required in order to fit the data of Dibb et al [7], whereas the gray lines indicate dependencies that are known to exist but found to be unnecessary to fit the data of Dibb et al [7] (solid lines are dependencies that were actually tested, and dotted lines indicate dependencies that were not considered in the model). Data (circles) are from Saraiva et al [36] and represent the percentage increase in LCC current from baseline following a dose of isoprenaline. It is assumed here that I LCC increase is linearly related to LCC phosphorylation fraction.…”
Section: Camkii Pathwaymentioning
confidence: 99%
“…This dissociation was probably due to the differences of severity of hypertrophy. In the models of heart failure, the reaction of I Ca to isoproterenol is generally decreased [29,36]; thus its reaction might tend to be decreased when hypertrophy became severe and heart failure is prominent. Based on the fact that both I K and I Ca were enhanced by isoproterenol via the same β-stimulation cascade [22], it was difficult to explain the mechanism of the results in our study regarding why only I Ca was enhanced by isoproterenol when the phosphodiesterase activity increased in hypertrophic hearts.…”
Section: Arrhythmogenicity Induced By Isoproterenolmentioning
confidence: 99%